ATMOSFER SEBAGAI PEMBENTUK PENGALAMAN RUANG DI SENDANGSONO - Reinaldi Primanizar; Alya Herlinda Putri; Ardinar Restu Fauzi (Jurnal Arsitektur ARCADE, 2023)
Abstract: Sendangsono is one of the works that create an interesting space experience through the atmospheric space. This study tries to understand the atmosphere element of Sendangsono's space and how these elements create dialogue with human multisensory in creating spatial experience. This study found how spatial experience is built from strengthening the genius loci, the combination of spatial sequences and material uniqueness provides behavioral stimuli, as well as the mix between natural and natural elements. The dialogue between atmosphere element and human multisensory immerse user in explorative behavior and feelings of solemnity and relaxation.Keyword: Atmosphere, Spatial experience, Sendangsono, PhenomenologyAbstrak: Sendangsono merupakan salah satu karya yang menciptakan pengalaman ruang yang menarik melalui atmosfer ruang. Penelitian ini mencoba memahami atmosfer ruang Sendangsono serta bagaimana elemen tersebut berdialog dengan multisensori dalam membangun pengalaman ruang. Dalam penelitian ini ditemukan bagaimana pengalaman ruang dibangun dari penguatan genius loci, kombinasi sekuen ruang dan keunikan material yang menstimulus perilaku, serta bauran antara elemen natural dan alami. Dialog antara elemen arsitektural dan multisensori manusia mampu menghanyutkan pengguna pada perilaku eksploratif dan perasaan khidmat dan relaksasi.Kata Kunci: Atmosfer, Pengalaman ruang, Sendangsono, Fenomenologi